Comparative analysis on the Role of 2,4-dichlorophenoxyacetic acid in the expression of bioactive compounds in callus of capsicum frutescens - Jamilah Syafawati Yaacob; Muhammad Aiman Ramli; Muhamad Hafiz Abd Rahim; Abigail Marie Robert Selvaraj; Laavanya Nyanasaigran (Penerbit Universiti Kebangsaan Malaysia, 2022)
Plant cell culture technology serves as an effective alternative system for in vitro production of bioactive molecules, as it allows for the exploration of valuable compounds under a controlled environment. The present study was conducted to evaluate the effect of plant growth regulator (PGR); 2,4-dichlorophenoxyacetic acid (2,4-D) on the expression of compounds in coloured callus of Capsicum frutescens, a vital spice in various cuisines worldwide. The differential accumulation of compounds in the callus was analysed using liquid chromatography-mass spectrometry (LCMS) and the PGR concentration that resulted in the highest accumulation of the valuable compounds was identified. In this study, calli of various colours (cream, yellow and green) were successfully produced from C. frutescens through plant tissue culture. The increase in 2,4-D concentrations was found to increase callus growth index (GI) and specific growth rate (Sg ), where the highest GI (0.5690) and Sg (0.6348 mg/week) were observed in callus produced in media supplemented with 0.5 mg/L 2,4-D. LCMS data analyses showed that 19 compounds were detected in the callus, with 8 compounds (fatty acids and phenolics) were successfully identified, while the remaining 11 compounds were reported as unknowns. Yellow-coloured callus was observed to contain the highest number of compounds (18 compounds), while green callus contained the least (14 compounds). This analysis provides valuable information on the application of biotechnological tools such as plant tissue culture as an alternative for sustainable production of compounds with high bioactivity in Capsicum frutescens.